Impaired Decision Making in Alzheimer's Disease: A Deficit of Cognitive Strategy Selection?. (May 2014) - Hot, Pascal; Ramdeen, Kylee T.; Borg, Céline; Bollon, Thierry; Couturier, Pascal
To assess whether the decline of decision-making processes in people diagnosed with Alzheimer's disease (AD) is explained by the use of an inappropriate analytic strategy induced by their high level of uncertainty about their ability, we used happiness induction to activate an appropriate heuristic processing of information. Healthy older adults and AD patients performed the Iowa Gambling Task either in a standard condition or after viewing a funny film clip. Although AD patients had impaired performances in the standard condition, the happiness condition significantly increased AD patient performance level compared with that of the control subgroups. Additional analyses showed that uncertainty levels were reduced in happy AD patients and that performances in the Iowa Gambling Task were not due to impairment in executive or memory functions. We suggest that higher uncertainty levels in patients with mild AD, which induce an inappropriate analytic strategy, can be reduced through emotional remediation techniques.